Stigma scale of epilepsy: validation process Escala de estigma na epilepsia: processo de validação - Paula T. Fernandes; Priscila C.B. Salgado; Ana L.A. Noronha; Josemir W. Sander; Li M. Li (Arquivos de Neuro-Psiquiatria)
PURPOSE: To validate a Stigma Scale of Epilepsy (SSE). METHODS: The SSE was completed by 40 adult with epilepsy attending an Outpatient Epilepsy Clinic at the University Hospital of UNICAMP, and by 40 people from the community. People were interviewed on an individual basis; a psychologist read the questions to the subjects who wrote the answers in a sheet. The procedure was the same for all the subjects and completion took around ten minutes. RESULTS: The SSE has 24 items. The internal consistency of the SSE showed alpha Cronbach’s coefficient 0.88 for the patients with epilepsy and 0.81 for the community. The overall mean scores of the Stigma Scale of Epilepsy formula were: 46 (SD=18.22) for patients and 49 (SD=13.25) for the community where a score of 0 would suggest no stigma, and 100 maximum stigma. DISCUSSION: The SSE has satisfactory content validity and high internal consistency. It allows the quantification of the perception of stigma by patients and people from community; this can then be used for interventional studies, such as mass media campaign in minimizing the negative facets of stigma. OBJETIVO: Validar a Escala de Estigma na Epilepsia (EEE). MÉTODO: A EEE foi aplicada em 40 pacientes adultos com o diagnóstico de Epilepsia do Ambulatório de Epilepsia do HC/Unicamp e em 40 pessoas da comunidade em geral. Os sujeitos foram entrevistados individualmente pelas psicólogas, que foram lendo as questões e anotando as respostas na escala. As condições de aplicação foram as mesmas e a aplicação durou cerca de 10 minutos. RESULTADOS: A EEE possui 24 itens. A consistência interna da EEE mostrou alfa de Cronbach, de 0,88 para os pacientes com epilepsia e 0,81 para a comunidade. As médias do valor geral de estigma obtido com a fórmula da EEE foram: 46 (DP=18,22) para os pacientes e 49 (DP=13,25) para a comunidade. DISCUSSÃO: A EEE possui uma satisfatória validade e alta consistência interna. Isso permite uma quantificação da percepção de estigma da epilepsia na comunidade em geral, que pode ser utilizada para estudos interventivos, como campanhas na mídia, para minimizar as facetas negativas do estigma na sociedade.